Prevalence of BRCA1 and BRCA2 mutations in unselected breast cancer patients from Peru. (28th October 2014) - Abugattas, J.; Llacuachaqui, M.; Allende, Y. Sullcahuaman; Velásquez, A. Arias; Velarde, R.; Cotrina, J.; Garcés, M.; León, M.; Calderón, G.; de la Cruz, M.; Mora, P.; Royer, R.; et al.
<x xml:space="preserve">Abstract</x> The prevalence of BRCA1 and BRCA2 mutations among breast cancer patients in Peru has not yet been explored. We enrolled 266 women with breast cancer from a National cancer hospital in Lima, Peru, unselected for age or family history. DNA was screened with a panel of 114 recurrent Hispanic BRCA mutations (HISPANEL). Among the 266 cases, 13 deleterious mutations were identified (11 in BRCA1 and 2 in BRCA2), representing 5% of the total. The average age of breast cancer in the mutation‐positive cases was 44 years. BRCA1 185delAG represented 7 of 11 mutations in BRCA1. Other mutations detected in BRCA1 included: two 2080delA, one 943ins10, and one 3878delTA. The BRCA2 3036del4 mutation was seen in two patients. Given the relatively low cost of the HISPANEL test, one should consider offering this test to all Peruvian women with breast or ovarian cancer.